Urgency of Transparency Regulation and Informed Consent in the Use of AI-Based Medical Chatbots in Indonesia - Narendra Bintang Khatulistiwa; Aan Platino; Mohamad Rosidi; Aris Prio Agus Santoso (Eastasouth Institute, 2026)
The rapid development of artificial intelligence technology has significantly transformed the healthcare sector, including the emergence of AI-based medical chatbots used for diagnosis support, symptom checking, health consultation, and patient education. In Indonesia, the adoption of medical chatbots has increased alongside the expansion of digital health services. However, the legal framework governing transparency obligations and informed consent mechanisms in the operation of AI-based medical chatbots remains fragmented and insufficient. This study analyzes the urgency of establishing comprehensive regulations concerning transparency and informed consent in the use of medical chatbots in Indonesia. The research employs a normative juridical method through statutory, conceptual, and comparative approaches. The study examines Indonesian laws relating to health services, electronic information systems, personal data protection, consumer protection, and medical ethics. The findings indicate that AI-based medical chatbots may create legal uncertainty regarding accountability, patient autonomy, data privacy, algorithmic bias, and medical malpractice risks when transparency and informed consent principles are not adequately regulated. Furthermore, existing regulations have not specifically addressed the obligations of developers and healthcare providers to disclose AI system limitations, decision-making processes, data usage practices, and potential risks to users. Therefore, Indonesia urgently requires a specific and harmonized regulatory framework to ensure legal certainty, patient protection, ethical healthcare innovation, and responsible AI governance. This article recommends the formulation of detailed transparency standards, mandatory informed consent procedures, algorithmic accountability principles, and supervisory mechanisms to support the safe and ethical implementation of AI-based medical chatbots in Indonesia.